2020
DOI: 10.1371/journal.pone.0227834
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of brain derived neurotrophic factor (BDNF) in obstructive sleep apnea syndrome (OSAS) patients

Abstract: Obstructive sleep apnea syndrome (OSAS) is a common disorder characterized by repeated episodes of upper airways collapse during the sleep. The following intermittent hypoxia triggers a state of chronic inflammation, which also interests the nervous system leading to neuronal damage and increased risk of cognitive impairment. Brain derived neurotrophic factor (BDNF) is a growth factor often associated with neuroplasticity and neuroprotection whose levels increase in several condition associated with neuronal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 28 publications
5
23
1
1
Order By: Relevance
“…The cytokines released by glial cells can further disrupt the BBB, and activate glial cells, leading to a vicious cycle. Evidence has shown that the inflammatory responses in an animal model of surgery result in decreased levels of BDNF, which is crucial in multiple aspects of neural plasticity [ 125 , 162 ]. Hippocampus, which is implicated in learning and memory function, appears particularly vulnerable to excessive neuroinflammation due to abundant receptors such as IL-1β receptor, TNF-α receptor, and HMGB1 receptor in this region [ 163 ].…”
Section: Role Of Inflammation In the Development Of Cognitive Dysfuncmentioning
confidence: 99%
“…The cytokines released by glial cells can further disrupt the BBB, and activate glial cells, leading to a vicious cycle. Evidence has shown that the inflammatory responses in an animal model of surgery result in decreased levels of BDNF, which is crucial in multiple aspects of neural plasticity [ 125 , 162 ]. Hippocampus, which is implicated in learning and memory function, appears particularly vulnerable to excessive neuroinflammation due to abundant receptors such as IL-1β receptor, TNF-α receptor, and HMGB1 receptor in this region [ 163 ].…”
Section: Role Of Inflammation In the Development Of Cognitive Dysfuncmentioning
confidence: 99%
“…Few BDNF polymorphisms are described; in particular, Val66Met is associated with lower BDNF expression, which can be related to alterations in neuronal recovery after injury. Sleep disorders can affect BDNF expression [ 58 , 59 ]. Acute sleep deprivation was shown to induce an increase in BDNF expression, which can be used for ischemic pre/postconditioning [ 60 ] in brain injuries, although this needs further examination.…”
Section: Circadian Regulation Clock Genes and Strokementioning
confidence: 99%
“…BDNF is a neurotrophic factor, acting on neurons. It supports survival and promotes the growth and differentiation of newly formed neurons and synapses (Flores et al, 2020 ). IGF-1 inhibits apoptosis and promotes proliferation and differentiation of neural stem cells (Thored et al, 2009 ).…”
Section: Microgliamentioning
confidence: 99%